Trabeculectomy with mitomycin C in uveitic glaucoma: a systematic review - Maha Said; Joshua Blair; Kamel M Soliman; Ahmed M Fathalla; Khaled Abdelazem; Alastair K Denniston (Delta Journal of Ophthalmology, 2021)
Background Glaucoma is a nonreversible optic neuropathy that may occur primarily or secondary to ocular pathology. Uveitis is a major etiological factor for secondary glaucoma, arising either owing to the inflammation itself or resulting from therapeutic steroid use. Many patients with uveitic glaucoma ultimately require a surgical intervention to maintain optimal intraocular pressures (IOP), often after treatment failure with multiple ocular antihypertensive agents. A leading surgical option for such patients is trabeculectomy augmented by intraoperative administration of mitomycin C (MMC). However, in the context of uveitic glaucoma, the relative merit of trabeculectomy with MMC compared with alternative surgical techniques, such as valve implantation, remains a subject of debate among ophthalmic surgeons. Study design This is a review of the literature to evaluate the efficacy and safety of trabeculectomy with MMC in uveitic glaucoma. Materials and methods A literature review of the use of trabeculectomy with MMC administration as an initial surgical management for uveitic glaucoma in adults was performed. Articles were identified by searches of PubMed and the Cochrane Library, using a strategy that defined the target condition (uveitis OR uveitic glaucoma OR inflammatory glaucoma) AND the intervention (trabeculectomy); limitation to MMC-augmented trabeculectomy was undertaken at the abstract and full-text stage. Data extracted included age of the patients, nature of the uveitis, preoperative status in terms of IOP and number of ocular hypotensive medications used, outcomes at annual time-points including IOP, number of ocular hypotensive medications, and surgical success (defined in terms of IOP) up to 5 years postoperatively. Adverse events were also recorded. Results The search strategy identified 498 papers, of which 32 were duplicates, 431 were excluded at abstract stage, and 28 were excluded at full-text stage; five of the 28 satisfied the inclusion criteria but were found to contain data that were entirely or largely contained within one of the other included papers. A total of seven studies were included, comprising 300 patients, with a weighted mean age of 45.8 years (range=30.0–56.9 years), and a range of uveitis syndromes including idiopathic (30%), Behcet’s disease (24.3%), Fuchs’ heterochromic uveitis (13.7%), and Vogt-Koyanagi-Harada syndrome (12.3%). Preoperative IOP and number of medications were reported in all studies. The mean (weighted) preoperative IOP was 34.2 mmHg (range=26.8–39.5 mmHg) and the mean (weighted) number of medications was 3.4 (range=2.3–4.5). Postoperative data were variably reported across the studies; the mean IOP at 1 year was reported in five studies (range=13.8–18.5 mmHg), the mean number of medications at 1 year was reported in four studies (range=0.3–2.6), and surgical success was variably defined preventing direct comparison or aggregation. Conclusion There is limited evidence to evaluate trabeculectomy with MMC as an initial surgical intervention for uveitic glaucoma, with the available evidence being derived entirely from retrospective studies, most of which do not have a parallel comparator group. Variation in reporting limits direct comparison and aggregation of these studies. Comparison between before and after intervention provides some limited evidence of effectiveness and safety. So, there is a need for well-designed prospective randomized controlled trials with long-term follow-up to compare interventions in this vulnerable group of patients.